Kepuasan Kerja Terhadap Organizational Citizenship Behavior (OCB) pada Pegawai Dinas Tata Ruang dan Cipta Karya - Rohaeni, Heni; Rosmawati, Mita (Laboratorium Administrasi Publik FISIP Universitas Andalas, 2019)
The performance of an organization is determined by the performance of employees. The Organization contribution in creating job satisfaction is needed, so the performance that produced by employees can be maximized. Besides the job satisfaction that can support the performance of a company, extra-role behavior or what is called Organizational Citizenship Behavior has a positive impact for the company. Organizational Citizenship Behavior (OCB) can arise from internal factors that come from the employee’s itself, one of them is job satisfaction perceived by the employees. Dinas Tata Ruang dan Cipta Karya Kota Bandung, as one of government agencies also expects its employees to have Organizational Citizenship Behavior. This study aims to determine the relationship of job satisfaction with Organizational Citizenship Behavior. The method used in this study is quantitative descriptive method. The data analysis method used is the correlation coefficient test, test the coefficient of determination, and test regression equation. Based on the result of research, job satisfaction has a relationship which in a very weak level of correlation with Organizational Citizenship Behavior.